2022
DOI: 10.1016/j.adro.2021.100795
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy in Conjunction With Surgical Stabilization of Impending or Pathologic Fractures Secondary to Metastasis: Is There a Difference Between Single and Multifraction Regimens?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…As PORT is considered the standard of care, much of the research has related to the ideal dose and fractionation, which is also unclear in the literature. Two recent studies indicate different results, specifically that a single fraction is equivalent to multiple fractions [21] and, alternatively, that PORT using 30 Gy in 10 fractions is preferred [22].…”
Section: Discussionmentioning
confidence: 99%
“…As PORT is considered the standard of care, much of the research has related to the ideal dose and fractionation, which is also unclear in the literature. Two recent studies indicate different results, specifically that a single fraction is equivalent to multiple fractions [21] and, alternatively, that PORT using 30 Gy in 10 fractions is preferred [22].…”
Section: Discussionmentioning
confidence: 99%
“…The role of postoperative radiotherapy in patients with surgically stabilized metastatic bone disease has been shown in a retrospective study in which recovery of normal functional status was significantly better for the group having surgery plus postoperative radiotherapy compared to radiotherapy only [93]. A second retrospective study has confirmed this effect [94]. However, it should be noted that the quality of evidence is low, due to the design of both studies (Willeumier et al 2016).…”
Section: Recommendationsmentioning
confidence: 97%